Exploring the Genetic Consequences of Clonality in Haplodiplontic Taxa. (29th January 2021) - Krueger-Hadfield, Stacy A; Guillemin, Marie-Laure; Destombe, Christophe; Valero, Myriam; Stoeckel, Solenn
Abstract: Partially clonality is an incredibly common reproductive mode found across all the major eukaryotic lineages. Yet, population genetic theory is based on exclusive sexuality or exclusive asexuality, and partial clonality is often ignored. This is particularly true in haplodiplontic eukaryotes, including algae, ferns, mosses, and fungi, where somatic development occurs in both the haploid and diploid stages. Haplodiplontic life cycles are predicted to be correlated with asexuality, but tests of this prediction are rare. Moreover, there are unique consequences of having long-lived haploid and diploid stages in the same life cycle. For example, clonal processes uncouple the life cycle such that the repetition of the diploid stage via clonality leads to the loss of the haploid stage. Here, we surveyed the literature to find studies that had genotyped both haploid and diploid stages and recalculated population genetic summary metrics for seven red algae, one green alga, three brown algae, and three mosses. We compared these data to recent simulations that explicitly addressed the population genetic consequences of partial clonality in haplodiplontic life cycles. Not only was partial clonality found to act as a homogenizing force, but the combined effects of proportion of haploids, rate of clonality, and the relative strength of mutation versus genetic drift impacts the distributions of population genetic indices. We found remarkably similar patterns across commonly used population genetic metrics between our empirical and recent theoretical expectations. To facilitate future studies, we provide some recommendations for sampling and analyzing population genetic parameters for haplodiplontic taxa.